THE IMPLEMENTATION OF VALUES COMPREHENSIVE APPROACH IN DEVELOPING CHARACTER IN AN ELEMENTARY SCHOOL IN BANYUWANGI (An Observational Report) - Zidniyati, Zidniyati (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
This is the sixth year for Tabita Puri Elementary School in applying character education. The implementation of character education in this school uses the values comprehensive approach introduced by Kirschenbaum. Based on the results obtained through observation, the application of character education in this school is close to perfection in achieving the target. Nevertheless, there are some targets that have not been reached. The focus of this paper is what factors affect some of the unachieved targets. There are at least four factors that contribute to the achievement of the targets of the character education program, including the pattern of approaches by teachers to students and parents; parent-school collaboration forms; social media and peers; and the presence of government participation. The purpose of this writing is to know how successful the application of character education in this school.